The concept of internet of things and its challenges to privacy - Mohamed, Sidi Mohamed Ould; Zulhuda, Sonny (2015)
This paper attempts to discuss the concept of the Internet of Things (IoT) from various aspects -including its pros and cons- in order to clarify the term as it is used by the experts and researchers. In addition to that, the paper also goes further to touch upon the IoT’s challenges to privacy from legal perspective. Last but not least, the paper provides recommendations on how to protect privacy and reap IoT advantages.